Neuron-glia cell adhesion molecule interacts with neurons and astroglia via different binding mechanisms (The Rockefeller University Press, 1988)
The neuron-glia cell adhesion molecule (Ng-CAM) is present in the central nervous system on postmitotic neurons and in the periphery on neurons and Schwann cells. It has been implicated in binding between neurons and between neurons and glia. To understand the molecular mechanisms of Ng-CAM binding, we analyzed the aggregation of chick Ng- CAM either immobilized on 0.5-micron beads (Covaspheres) or reconstituted into liposomes. The results were correlated with the binding of these particles to different types of cells as well as with cell-cell binding itself. Both Ng-CAM-Covaspheres and Ng-CAM liposomes individually self-aggregated, and antibodies against Ng-CAM strongly inhibited their aggregation; the rate of aggregation increased approximately with the square of the concentration of the beads or the liposomes. Much higher rates of aggregation were observed when the ratio of Ng-CAM to lipid in the liposome was increased. Radioiodinated Ng-CAM on Covaspheres and in liposomes bound both to neurons and to glial cells and in each case antibodies against Ng-CAM inhibited 50-90% of the binding. Control preparations of fibroblasts and meningeal cells did not exhibit significant binding. Adhesion between neurons and glia within and across species (chick and mouse) was explored in cellular assays after defining markers for each cell type, and optimal conditions of shear, temperature, and cell density. As previously noted using chick cells (Grumet, M., S. Hoffman, C.-M. Chuong, and G. M. Edelman. 1984 Proc. Natl. Acad. Sci. USA. 81:7989-7993), anti-Ng-CAM antibodies inhibited neuron-neuron and neuron-glia binding. In cross- species adhesion assays, binding of chick neurons to mouse astroglia and binding of mouse neurons to chick astroglia were both inhibited by anti-Ng-CAM antibodies. To identify whether the cellular ligands for Ng- CAM differed for neuron-neuron and neuron-glia binding, cells were preincubated with specific antibodies, the antibodies were removed by washing, and Ng-CAM-Covasphere binding was measured. Preincubation of neurons with anti-Ng-CAM antibodies inhibited Ng-CAM-Covasphere binding but similar preincubation of astroglial cells did not inhibit binding. In contrast, preincubation of astroglia with anti-astroglial cell antibodies inhibited binding to these cells but preincubation of neurons with these antibodies had no effect. Together with the data on Covaspheres and liposome aggregation, these findings suggested that Ng- CAM-Covaspheres bound to Ng-CAM on neurons but bound to different molecules on astroglia.(ABSTRACT TRUNCATED AT 400 WORDS)